DAMPAK REKLAMASI PEMBANGUNAN TANGGUL LAUT TERHADAP PEREMPUAN BURUH PEMIPIL KERANG - Kristina Magdalena Pakpahan (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Since 1995, reclamation has been used by the government to provide new land areas for settlements, ports, urban areas, tourism areas, etc. Proponents of reclamation have mentioned several positive benefits of reclamation: creating new land, developing tourism, improving the economy of communities around the coast, increasing employment, increasing productive land, and helping improve aquatic habitats. However, reclamation also has negative impacts: eliminating fishermen's livelihoods, causing water pollution, destroying ecosystems, and eliminating access to fishing grounds.  Out of many negative impacts of reclamation, what has not been widely discussed is the negative impact on women, especially women who work in post-production sector. This article aims to fill this research gap. This article raises the results of a study on the negative impact of sea wall reclamation on female clam shellers in coastal area of Kalibaru, Cilincing, North Jakarta. Based on data collected using the Feminist Participatory Action Research (FPAR) approach with the FGD and in-depth interview methods, various impacts of the sea wall construction were found felt by women shellfish workers: economic impacts, psychological impacts, ecological impacts, socio-cultural impacts, etc. This article focuses on discussing the impact of sea wall construction reclamation on female clam shellers by highlighting the conditions before and after the construction of the sea wall, and the differences in the impacts and effects of sea wall construction based on gender using a feminist political ecology approach.